Enhancing Monacolin K and GABA Biosynthesis in Monascus pilosus via GAD Overexpression: Multi-Omics Elucidation of Regulatory Mechanisms - Wenlan Mo; Yiyang Cai; Simei Huang; Lishi Xiao; Yanfang Ye; Bin Yang; Chan Zhang; Zhiwei Huang (Journal of Fungi)
Monascus produces various bioactive compounds, including monacolin K (MK), γ-aminobutyric acid (GABA), and Monascus pigments (MPs). Studies have shown that overexpressing genes within the MK biosynthetic cluster significantly enhances MK production. Additionally, MK synthesis in Monascus is regulated by other genes. Based on previous transcriptomic analyses conducted in our laboratory, a significant positive correlation was identified between the expression level of the GAD gene and MK production in M. pilosus. In this study, the GAD gene from M. pilosus was selected for overexpression, and a series of engineered M. pilosus strains were constructed. Among the 20 PCR-positive transformants obtained, 13 strains exhibited MK production increases of 12.84–52.50% compared to the parental strain, while 17 strains showed GABA production increases of 17.47–134.14%. To elucidate the molecular mechanisms underlying the enhanced production of MK and GABA, multi-omics analyses were performed. The results indicated that GAD overexpression likely promotes MK and GABA synthesis in M. pilosus by regulating key genes (e.g., HPD, HGD, and FAH) and metabolites (e.g., α-D-ribose-1-phosphate, β-alanine) involved in pathways such as tyrosine metabolism, phenylalanine metabolism, the pentose phosphate pathway, propanoate metabolism, and β-alanine metabolism. These findings provide theoretical insights into the regulatory mechanisms of MK and GABA biosynthesis in Monascus and suggest potential strategies for enhancing their production.